Silicon-carbon composite material, preparation method and application thereof, and lithium ion battery
By using chemical vapor deposition method to deposit silicon and grow carbon nanotubes in lithium-ion batteries, the problems of low first efficiency, insufficient single-particle strength and excessive expansion of silicon carbon anode materials are solved, and silicon-carbon composite materials with high conductivity, mechanical strength and expansion suppression are achieved, improving the overall performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411998028.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing silicon-carbon anode materials have problems such as low first effect, insufficient single particle strength, and excessive expansion, which makes it difficult to popularize their application in lithium-ion batteries.
The prelithiated porous carbon was deposited by chemical vapor deposition method, and the passivation layer was coated after the silicon was deposited. Then, alkaline reagents and transition metal salts were added to the mixed solution to carry out in situ growth of carbon nanotubes and the formation of carbon layers, and finally obtain a silicon-carbon composite material through polymerization and carbonization treatment.
The conductivity and mechanical strength of silicon-carbon composite materials are improved, the expansion performance is suppressed, and the first-effect, capacity, rate performance and cycling performance of lithium-ion batteries are enhanced.
Smart Images

Figure CN119797369A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon composite material, a preparation method thereof, an application thereof and a lithium ion battery. Background Art
[0002] Silicon-carbon anode materials have attracted wide attention due to their extremely high gram capacity and volume energy density. They have become an important means to rapidly increase battery energy density at this stage and are widely used in the 3C field and the power field. However, they have important drawbacks, one of which is their low initial efficiency, another is their low single particle strength, and the third is their large expansion due to lithium insertion. These three important drawbacks make their application difficult to popularize. Currently, only about 15% of lithium-ion anode materials can be doped to take into account various performances.
[0003] The reason for these three drawbacks is that when depositing silane on porous carbon with a large pore volume, sufficient filling can easily cause it to expand too much, and although insufficient filling can alleviate the expansion, it also has the problem of insufficient single particle strength and low initial efficiency. In addition, because it is difficult to make the surface passivation layer thicker, the strength of the coating layer of the current acetylene-coated silicon-carbon negative electrode material is insufficient. Even if the strength of the coating layer is strengthened through long-term passivation coating, it affects the rate and is difficult to meet the current terminal requirements. Finally, even if the silicon-carbon negative electrode material with a large pore volume is successfully pre-lithiated, because the lithium insertion mechanism of the silicon material is in the form of an alloy, it is very unstable after pre-lithiation, and it has a series of application problems such as spontaneous combustion, bubble generation when stirred, and automatic reduction of the initial efficiency when naturally placed.
[0004] If we can design a silicon-carbon negative electrode material that integrates single-particle strength, gram capacity, first efficiency, rate, expansion and other aspects, it will enable the application of silicon-carbon negative electrodes to grow exponentially and have important economic value. Summary of the invention
[0005] In order to solve the above problems existing in the existing silicon-carbon materials, the present invention provides a silicon-carbon composite material and its preparation method, application and lithium-ion battery. The silicon-carbon composite material has good conductivity and mechanical strength, and excellent expansion inhibition performance, and the prepared lithium-ion battery can take into account excellent first efficiency, gram capacity, rate performance and cycle performance.
[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.
[0007] The present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps:
[0008] S1, using chemical vapor deposition to deposit silicon on the pre-lithiated porous carbon to obtain a first precursor;
[0009] S2, coating the surface of the first precursor with a passivation layer to obtain a second precursor;
[0010] S3, adding an alkaline reagent to a mixed solution containing the second precursor, a transition metal salt and a solvent, and drying to obtain a third precursor;
[0011] S4, performing carbon deposition on the third precursor by chemical vapor deposition to in-situ grow carbon nanotubes to obtain a fourth precursor;
[0012] S5, subjecting the slurry containing the fourth precursor, the phenolic compound and the aldehyde compound to a polymerization reaction, and then subjecting the slurry to a carbonization treatment after drying, to obtain the silicon-carbon composite material.
[0013] In step S1, the use of pre-lithiated porous carbon can not only improve the initial effect, but also shrink the gaps. In the subsequent silicon deposition process, silicon is deposited into the porous carbon in an adaptive manner, that is, the amount of silicon deposited in the micropores is reduced and increased in the mesopores. This step can greatly reduce expansion and further nano-size the deposition of silicon nanoparticles, thereby increasing the rate.
[0014] In step S1, the pre-lithiated porous carbon can be prepared by conventional methods.
[0015] In some preferred embodiments, the pre-lithiation method comprises mixing the porous carbon and a lithium source and heating the mixture.
[0016] Among them, the lithium source preferably includes one or more of phenyl lithium, lithium chloride, lithium sulfate, lithium carbonate, lithium acetate, lithium bromide, lithium iodide, lithium nitrate, lithium phosphate, lithium sulfate, lithium bisulfite, lithium citrate and lithium hydride, for example, phenyl lithium.
[0017] The heating temperature is between the melting point of the lithium source and the decomposition temperature of the lithium source. At the heating temperature, the lithium source will melt, but will not undergo a chemical reaction, i.e., will not decompose, and then the melted lithium source will enter the porous carbon.
[0018] In some specific embodiments, the lithium source is phenyllithium, and the heating temperature is 140-165°C, for example, 150°C.
[0019] The mass ratio of the porous carbon to the lithium source is preferably 1:(0.1-0.6), for example 1:0.42.
[0020] The pre-lithiation process is preferably carried out under the protection of an inert gas. The inert gas is, for example, argon. The ventilation volume of the inert gas is preferably 0.2-5 L·kg -1 ·min -1 , for example 2L·kg -1 ·min-1 Among them, "L·kg -1 min -1 ” refers to the volume of inert gas introduced per minute per kilogram of porous carbon.
[0021] In the present invention, the pre-lithiation process can be carried out in a closed environment.
[0022] In step S1, the temperature of silicon deposition is preferably 400-800°C, for example 500°C.
[0023] In step S1, the silicon deposition time is preferably 4-20 hours, for example 10 hours.
[0024] In step S1, the silicon source for the silicon deposition may include silane, and the silane preferably includes one or more of monosilane, disilane, trisilane and tetrasilane.
[0025] In step S1, during the silicon deposition process, the ventilation volume of the silicon source is preferably 0.04-0.4 L·kg -1 min -1 Among them, "L·kg -1 min -1 ” refers to the volume of silicon source introduced per minute per kilogram of pre-lithiated porous carbon.
[0026] In step S1, preferably, the gas source for silicon deposition includes a silicon source and a carrier gas; wherein the volume ratio of the silicon source to the carrier gas is 1:(2-6), for example, 1:4.
[0027] In the present invention, in step S2, the passivation layer preferably includes a carbon layer and / or an oxide layer.
[0028] In some preferred embodiments, the passivation layer is a carbon layer. Preferably, the carbon layer is obtained by carbon deposition using a chemical vapor deposition method.
[0029] The carbon source of the carbon deposition preferably includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates, such as acetylene.
[0030] In the process of carbon deposition, the ventilation volume of the carbon source is preferably 0.1-10 L·kg -1 ·min -1 , for example 1L kg -1 ·min -1 Among them, "L·kg -1 min -1 ” refers to the volume of the carbon source introduced per minute per kilogram of the first precursor.
[0031] The carbon deposition time is preferably 4-20 hours, such as 10 hours.
[0032] The carbon deposition temperature is preferably 400-800°C, such as 500°C.
[0033] After the carbon deposition, preferably, it is also preferably purged with an inert atmosphere and cooled. The inert atmosphere is, for example, nitrogen. The cooling is preferably cooled to -40°C to 100°C, for example, to 25°C.
[0034] In the present invention, in step S3, the transition metal salt reacts with an alkaline reagent to generate nano transition metal oxides. During the reaction, the nano transition metal oxides are generated in the mesopores and macropores of the second precursor first, and then on the surface.
[0035] In the present invention, the transition metal salt may be a soluble salt of a transition metal conventional in the art that can catalyze the growth of carbon nanotubes in the form of an oxide or a single substance.
[0036] In step S3, the transition metal salt preferably includes one or more of iron salt, nickel salt and cobalt salt.
[0037] In step S3, the transition metal salt may include a divalent salt and / or a trivalent salt of a transition metal.
[0038] In some preferred embodiments, in step S3, the transition metal salt includes a divalent salt and a trivalent salt of iron; wherein the molar ratio of the divalent salt to the trivalent salt of iron is preferably (2-4):1.
[0039] In step S3, the transition metal salt preferably includes one or more of transition metal hydrochlorides, transition metal nitrates, transition metal sulfates, transition metal acetates and transition metal citrates.
[0040] In some specific embodiments, the transition metal salt comprises ferrous sulfate and ferric chloride, wherein the molar ratio of ferrous sulfate to ferric chloride is preferably (2-4):1.
[0041] In step S3, the content of the transition metal salt is preferably 0.01-0.3 mol / kg, for example 0.06 mol / kg, and the content is the molar number of the transition metal element in the transition metal salt relative to 1 kg of the second precursor.
[0042] In step S3, the alkaline reagent may include a weak base reagent and / or a strong base reagent, preferably ammonia water.
[0043] The concentration of the ammonia water is preferably 1-10%, such as 5%, where the percentage is the mass of ammonia to the total mass of the ammonia water.
[0044] In step S3, the mass ratio of the alkaline reagent to the solvent is preferably (1-1000):100, for example, 1:1.
[0045] In step S3, the mixed solution preferably also includes a complexing agent. Based on the complexing effect of the complexing agent, the nano-size and uniformity of the transition metal oxide in the reaction can be greatly promoted, and its agglomeration phenomenon can be further alleviated. In addition, when the complexing agent is added, the complexing agent is coated on the surface of the second precursor, and some oxygen-containing groups will be retained after carbonization. The hydrogen bonds and van der Waals forces between the complexing agent and the polar binder are stronger, and the bonding effect is stronger, which can inhibit powder loss; when the complexing agent contains metal atoms, it is easy to change the smoothness of the subsequent coated carbon layer after carbonization, increase the contact degree between the subsequent coated carbon layer and the surface of the second precursor, and is more conducive to the improvement of the strength of the subsequent coated carbon layer; and the doping of metal atoms in the coated carbon layer has the effect of transforming the carbon material into amorphous carbon, changing the disordered structure of the amorphous carbon material, and effectively inhibiting the buffering stress and expansion of the surface of the silicon-carbon composite material, and improving the pressure resistance of the silicon-carbon composite material.
[0046] The complexing agent may include an organic acid and / or an organic acid salt, preferably one or more of acetic acid, citric acid, EDTA and salts thereof, for example, one or more of ferric acetate, sodium acetate, ferric citrate, sodium citrate and EDTA.
[0047] Wherein, the mass ratio of the complexing agent to the second precursor is preferably 1:(5-1000), for example 1:10.
[0048] In step S3, the solvent is preferably deionized water.
[0049] In step S3, the mass ratio of the second precursor to the solvent is preferably 1:(5-50), for example 1:10.
[0050] In step S3, the adding is preferably performed under stirring conditions.
[0051] Wherein, the stirring speed is preferably 100-1000r / min, for example 300r / min.
[0052] In step S3, the alkaline reagent is preferably added dropwise, and the alkaline reagent is added at a rate of 1-1000 mL / min, such as 10 mL / min.
[0053] In step S3, the operation of adding the alkaline reagent is preferably performed under a protective atmosphere. The protective atmosphere preferably includes one or more of an inert atmosphere, a reducing atmosphere and a carbon dioxide atmosphere, for example, one or more of nitrogen, argon, helium, hydrogen and carbon monoxide.
[0054] In step S3, the method for preparing the mixed solution may include: immersing the second precursor in a solvent, and then adding a transition metal salt to obtain a mixed solution.
[0055] In step S3, the drying can be performed by conventional methods in the art, preferably spray drying.
[0056] In step S3, the drying speed may be 0.1-10 kg / h, for example, 1 kg / h.
[0057] In step S3, the drying temperature is preferably 50-300°C, for example 200°C.
[0058] In step S3, the drying may be performed under a protective atmosphere, such as nitrogen.
[0059] In step S3, the Dv50 particle size of the third precursor may be 4-20 μm, for example, 8 μm.
[0060] In step S3, after adding the alkaline reagent and before drying, an alcoholization step is preferably further included. The alcoholization step can further increase the degree of reaction of the transition metal salt to form the transition metal oxide. The alcoholization temperature is preferably 50-100° C., such as 90° C.; the alcoholization time is preferably 0.5-25 h, such as 5 h.
[0061] In the present invention, in step S4, the transition metal oxide in the third precursor and / or the transition metal element obtained after reduction can catalyze the in-situ growth of carbon nanotubes. While the carbon nanotubes are grown in-situ, the carbon coating process is carried out simultaneously. At this time, the grown carbon nanotubes can grow in the form of embedded carbon layers, and after protruding out of the carbon layer, it is helpful to carbon coat again, accelerate the coating speed, and thicken the carbon layer. Among them, when the carbon nanotubes are grown in-situ, whether the carbon nanotubes are single-walled carbon nanotubes or multi-walled carbon nanotubes depends on the loading amount of the transition metal, the uniformity of distribution, and the nano-degree of the transition metal oxide.
[0062] In step S4, the carbon nanotubes may include single-walled carbon nanotubes and / or multi-walled carbon nanotubes, wherein the pore size of the multi-walled carbon nanotubes is preferably 5-50 nm, and the pore size of the single-walled carbon nanotubes is preferably 2-20 nm.
[0063] In step S4, before the carbon deposition, a step of reducing the third precursor may be further included.
[0064] The reduction temperature is preferably 400-800°C, such as 550°C.
[0065] The reduction is preferably carried out in a reducing atmosphere; the reducing atmosphere is preferably hydrogen; the ventilation volume of the reducing atmosphere is preferably 0.1-10 L·kg -1 ·min -1 , for example 1L kg -1 ·min -1 Among them, "L·kg -1 min -1 ” refers to the volume of reducing atmosphere introduced per minute per kilogram of the third precursor.
[0066] The reduction time is preferably 60-300 min, for example 120 min.
[0067] In step S4, the carbon deposition may adopt a carbon source conventionally used for vapor deposition in the art, preferably including one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates, such as acetylene.
[0068] In step S4, during the carbon deposition process, the ventilation rate of the carbon source is preferably 0.2-20 L·kg -1 ·min -1 , for example 2L·kg -1 ·min -1 Among them, "L·kg -1 min -1 ” refers to the volume of the carbon source introduced per minute per kilogram of the third precursor.
[0069] In step S4, the carbon deposition time is preferably 60-300 min, for example 120 min.
[0070] In step S4, the temperature of the carbon deposition is preferably 400-800°C, for example 550°C.
[0071] In step S4, the specific surface area of the fourth precursor is preferably 300-400m 2 / g, for example, 349m 2 / g.
[0072] In step S4, the Dv50 particle size of the fourth precursor may be 4-20 μm, for example, 8.2 μm.
[0073] In the present invention, in step S5, the surface of the fourth precursor is coated with phenolic resin by in-situ polymerization and carbonized, which has the following advantages: first, by utilizing the spear-shaped anchoring effect of carbon nanotubes, the phenolic resin can be directionally induced to solidify on the surface of the fourth precursor having carbon nanotubes through the stake effect; second, by optionally adding acid to the slurry, the transition metal oxide and / or transition metal can be converted into a transition metal salt, and the transition metal salt can intensify the polymerization of the phenolic resin on its surface, thereby improving the strength of the coating layer; third, during the carbonization process, iron ions can catalyze the generation of graphitized carbon, and the shrinkage effect during the carbonization process can improve the conductivity of the outer carbon layer, and at the same time, it can also achieve the improvement of High material tap density reduces voids and improves strength; fourthly, based on the unstable behavior of lithium in porous carbon due to its easy diffusion, a lithium hydroxide layer is formed during the polymerization of the phenolic resin on the surface of the fourth precursor. This layer can be evenly covered between the passivation layer and the phenolic resin layer, thereby shielding the lithium inside the porous carbon from continuing to overflow and inhibiting the free diffusion of lithium. At the same time, during the carbonization process of the outer phenolic resin, it will decompose to form a solid electrolyte layer containing lithium oxide with high ionic conductivity, forming an artificial SEI film. This film can not only improve the rate performance and thermal cycle performance, but also improve the stability of the resulting silicon-carbon composite material during processing, and further enhance the single particle strength.
[0074] In step S5, the pH of the slurry may be 1-3, or the pH of the slurry may be 12-14. The pH of the slurry is achieved by adding acid or alkali.
[0075] In step S5, the slurry may further include alkali or acid.
[0076] In some optional embodiments, the slurry further includes an acid, such as hydrochloric acid, sulfuric acid or nitric acid.
[0077] In some optional embodiments, the slurry further includes a base.
[0078] The mass ratio of the base to the fourth precursor is preferably (0.1-1):1, such as 0.4:1.
[0079] The base may be a base commonly used in the art, preferably an alkali metal hydroxide or ammonia, such as sodium hydroxide.
[0080] In step S5, the solvent in the slurry is, for example, water.
[0081] In step S5, the mass ratio of the fourth precursor to the solvent in the slurry is 1:(5-15), for example, 1:9.
[0082] In step S5, the molar ratio of the phenolic compound to the aldehyde compound is preferably 1:(1-2), for example, 6:7.
[0083] In step S5, the mass ratio of the fourth precursor to the phenolic compound is preferably 100:(0.1-120), more preferably 100:(15-120), for example 100:17, 100:34, 100:68, 100:85, 100:102 or 100:119.
[0084] In step S5, the polymerization reaction temperature may be 40-100°C, for example, 80°C.
[0085] In step S5, the polymerization reaction time may be 6-600 min, for example, 300 min.
[0086] In step S5, the polymerization reaction may be carried out in a stirring device, and the rotation speed of the stirring device is preferably 100-1000 r / min, for example, 300 r / min.
[0087] In some preferred embodiments, in step S5, the phenolic compound is phenol, and the aldehyde compound is formaldehyde.
[0088] In step S5, the drying can be performed in a conventional manner in the art, preferably spray drying or vacuum drying.
[0089] In step S5, the carbonization treatment may be a conventional carbonization treatment in the art, preferably a staged heat treatment.
[0090] In some preferred embodiments, the carbonization process comprises the following stages:
[0091] The first stage: heat up to 150-250℃ at 1-10℃ / min, keep warm for 0.5-5h;
[0092] The second stage: heat up to 600-700℃ at 0.5-20℃ / min and keep warm for 5-20h.
[0093] In some specific embodiments, the carbonization process comprises the following stages:
[0094] The first stage: heating to 200℃ at a heating rate of 4℃ / min and keeping warm for 1h;
[0095] The second stage: heat up to 600℃ at a heating rate of 4℃ / min and keep warm for 12h.
[0096] In step S5, the carbonization may be performed under an inert atmosphere, and the inert atmosphere preferably includes one or more of nitrogen, helium and argon.
[0097] In the present invention, in step S5, the carbonization treatment preferably includes a pickling step. The pickling treatment after the carbonization treatment is beneficial to remove transition metals.
[0098] Wherein, the pickling preferably includes the step of washing with hydrochloric acid; the mass ratio of the hydrochloric acid to the product obtained by the carbonization treatment is (1-20):1, for example, 10:1; the concentration of the hydrochloric acid can be 0.1-10 mol / L, for example, 1 mol / L.
[0099] In the present invention, the porous carbon may be conventional porous carbon in the art.
[0100] In some embodiments, the porous carbon satisfies one or more of the following conditions: ① The specific surface area is 1400-2500m 2 / g, ② micropore volume accounts for 60-100%, ③ mesopore and above pore volume accounts for 0-40%, ④ pore volume is 0.6-1.4cm 3 / g.
[0101] In some specific embodiments, the porous carbon satisfies one or more of the following conditions: ① The specific surface area is 1890 m 2 / g, ② micropore volume accounts for 85.3%, ③ mesopore and above pore volume accounts for 14.7%, ④ pore volume is 1.32cm 3 / g.
[0102] In the present invention, the porous carbon can be prepared by conventional methods in the art. The carbon source of the porous carbon can include one or more of resin, sucrose, glucose, fructose, starch, cellulose, triglyceride, fatty acid, hemicellulose, lignin and asphalt, preferably resin, more preferably phenolic resin.
[0103] In some embodiments, the porous carbon is prepared using phenolic resin as a carbon source.
[0104] In some specific embodiments, the method for preparing porous carbon comprises the following steps:
[0105] (1) spray drying a slurry containing a phenolic resin to obtain a carbon material precursor;
[0106] (2) carbonizing the carbon material precursor to obtain a porous carbon precursor;
[0107] (3) Activating the porous carbon precursor to obtain porous carbon.
[0108] In step (1), the slurry may further include a curing agent and a solvent; the curing agent is, for example, hexamethylenetetramine, and the solvent is, for example, ethanol. The mass ratio of the phenolic resin to the curing agent is preferably 100:(1-20), for example, 100:6.
[0109] In step (1), the spray drying temperature is preferably 80-200°C, for example 130°C.
[0110] In step (1), the spray drying is preferably performed until the particles have a Dv50 particle size of 4-20 μm, for example 8 μm.
[0111] In step (2), the carbonization method may be a conventional carbonization method in the art, such as a staged heat treatment; preferably, the carbonization includes the following stages:
[0112] The first stage: heat up to 150-250℃ at 1-10℃ / min, keep warm for 0.5-5h;
[0113] The second stage: heat up to 600-700℃ at 0.5-20℃ / min and keep warm for 0.5-5h.
[0114] In some specific embodiments, the carbonization comprises the following stages:
[0115] The first stage: heating to 200℃ at a heating rate of 4℃ / min and keeping warm for 1h;
[0116] The second stage: increase the temperature to 652°C at a heating rate of 4°C / min and keep it at this temperature for 1h.
[0117] In step (2), the carbonization may be performed under an inert atmosphere, and the inert atmosphere preferably comprises one or more of nitrogen, helium and argon.
[0118] In step (3), the activation method can be a conventional activation pore-forming method in the art, such as alkali activation or gas activation, preferably gas activation.
[0119] The gas activation is preferably carbon dioxide activation or water vapor activation.
[0120] The ventilation volume of the gas activation is preferably 0.2-20 L·kg -1 ·min -1 , for example 2·L·kg -1 ·min -1 Among them, "L·kg -1 min -1 ” refers to the volume of activated gas introduced per minute per kilogram of porous carbon precursor.
[0121] The gas activation temperature is preferably 400-1000°C, for example 550°C.
[0122] The gas activation time is preferably 5-20 hours, for example 9 hours.
[0123] The present invention provides a silicon-carbon composite material, which is prepared by the method for preparing the silicon-carbon composite material as described above.
[0124] The present invention provides a silicon-carbon composite material, which may include a core-shell structure, wherein the core-shell structure includes an inner core and an outer shell covering the inner core, wherein the inner core includes pre-lithiated porous carbon and silicon particles, and the silicon particles are distributed in the pores of the pre-lithiated porous carbon; along the direction away from the inner core, the outer shell includes a passivation layer, a solid electrolyte layer and a graphitized carbon layer in sequence; wherein carbon nanotubes are distributed in the passivation layer and the solid electrolyte layer, and the carbon nanotubes penetrate the solid electrolyte layer.
[0125] In the present invention, the Dv50 particle size of the silicon-carbon composite material may be 8-10 μm, preferably 8-9 μm, for example, 8.3 μm, 8.4 μm, 8.5 μm, 8.7 μm or 8.9 μm.
[0126] In the present invention, the specific surface area of the silicon-carbon composite material can be 1-2m 2 / g, for example, 1.1m 2 / g, 1.2m 2 / g, 1.5m 2 / g or 1.6m 2 / g.
[0127] In the present invention, the carbon content of the silicon-carbon composite material may be 50%-60%, for example, 51.8%, 53.1%, 53.8%, 53.9%, 55.3%, 58.1% or 58.7%.
[0128] In the present invention, the oxygen content of the silicon-carbon composite material may be 0.2%-1.6%, for example, 0.3%, 0.5%, 0.7%, 0.8%, 1.1% or 1.4%.
[0129] In the present invention, the silicon content of the silicon-carbon composite material may be 30%-50%, preferably 35%-45%, for example, 35.4%, 36.1%, 39.1%, 40.7%, 40.5%, 41.6%, 43.5%.
[0130] In the present invention, the lithium content of the silicon-carbon composite material may be 4%-5%, for example, 4.3%, 4.4%, 4.5%, 4.6% or 4.8%.
[0131] In the present invention, the single particle strength of the silicon-carbon composite material may be 5-25 MPa, preferably 10-20 MPa, for example, 10.4 MPa, 14.3 MPa, 16.6 MPa, 16.9 MPa, 17.2 MPa, 17.5 MPa or 18.2 MPa.
[0132] In the present invention, the silicon-carbon composite material satisfying the above-mentioned structure, composition and performance parameters can be prepared by the aforementioned method for preparing the silicon-carbon composite material.
[0133] The present invention also provides a pole piece, which comprises the silicon-carbon composite material as described above.
[0134] The present invention provides an application of the silicon-carbon composite material as described above as a negative electrode material in a lithium-ion battery.
[0135] The present invention also provides a lithium ion battery, which comprises the silicon-carbon composite material as described above.
[0136] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0137] The reagents and raw materials used in the present invention are commercially available.
[0138] The positive and progressive effects of the present invention are:
[0139] In the preparation method of the silicon-carbon composite material of the present invention, the porous carbon is first pre-lithiated and then silicon is deposited, and by introducing a transition metal salt, the transition metal salt can induce the carbon to grow carbon nanotubes in situ during the subsequent carbon deposition, and on this basis, the phenolic resin is coated by in-situ polymerization and then carbonized to obtain a graphitized carbon layer. The obtained silicon-carbon composite material has good electrical conductivity and mechanical strength, and excellent expansion inhibition performance. The lithium-ion battery prepared by using the silicon-carbon composite material can take into account excellent first efficiency, gram capacity, rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0140] Figure 1 Schematic diagram of the structure of the silicon-carbon composite material obtained in Examples 1-7.
[0141] Reference numerals:
[0142] Prelithiated porous carbon 1
[0143] Silicon particles 2
[0144] Passivation layer 3
[0145] Solid electrolyte layer 4
[0146] Carbon Nanotubes 5
[0147] Graphitized carbon layer 6 DETAILED DESCRIPTION
[0148] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0149] In the following examples and comparative examples, the phenolic resin was purchased from Hubei Hengye Technology Co., Ltd., model 2135.
[0150] In the following examples and comparative examples, the preparation of porous carbon includes the following steps (the total step is recorded as S0):
[0151] (1) Preparation of carbon material precursor: 1 kg of phenolic resin, 2 kg of ethanol, and 60 g of hexamethylenetetramine (HMT) were mixed by a high-speed homogenizer at a speed of 2000 r / min for 60 min. The mixture was spray-dried at 130° C. until the particle size Dv50 was 8 μm.
[0152] (2) Carbonization: The spray-dried powder was placed in a rotary furnace for cross-linking at 10 r / min, and then carbonized. The heating curve in the first stage was 4°C / min, and the temperature was raised to 200°C and kept for 1 hour. The main purpose was to cross-link the phenolic resin. The heating curve in the second stage was 4°C / min, and the temperature was raised to 652°C and kept for 1 hour. The nitrogen atmosphere was protected and the ventilation volume was 1 L·kg -1 ·min -1 .
[0153] (3) Activation: In CO 2 The porous carbon was obtained by activation for 9 h in a furnace with a temperature of 550 °C and a ventilation volume of 2 L kg -1 ·min -1 The specific surface area of the porous carbon obtained is 1890m 2 / g, micropore volume accounts for 85.3%, mesopore volume accounts for 14.7%, and pore volume is 1.32cm 3 / g.
[0154] Example 1
[0155] S1. Preparation of the first precursor:
[0156] S1-1, pre-lithiation: 1 kg of the porous carbon prepared in step S0 was mixed with phenyl lithium in a mass ratio of 1:0.42, and argon gas was introduced at 150°C with a flow rate of 2 L kg -1 ·min -1 .
[0157] S1-2, the atmosphere was switched to a silane mixture (20% silane and 80% argon by mass), and the first precursor was formed by deposition at 500°C for 10 h. The ventilation volume of the silane mixture was 2 L kg -1 ·min -1 .
[0158] S2. Preparation of the second precursor:
[0159] The atmosphere was switched to an acetylene mixture (20% acetylene and 80% argon by mass), with a ventilation volume of 5 L kg -1 ·min -1 , continue to deposit at 500°C for 10 h, then switch to nitrogen, and then cool to room temperature 25°C to obtain the second precursor.
[0160] S3. Preparation of the third precursor:
[0161] S3-1, deposition of carbon nanotube catalyst: 1kg of the second precursor is immersed in 10kg of deionized water, 100g of complexing agent sodium citrate is added, 0.04mol of ferrous sulfate is added, ferric chloride is added at a molar ratio of 2:1, and then 1kg of 5% ammonia water is added, the titration rate is 10mL / min, and after titration, alcoholization is carried out at 90°C for 5h. The above deposition steps need to be carried out under stirring, the stirring speed is 300r / min, and nitrogen is used as the protective atmosphere for protection throughout the process.
[0162] S3-2, drying and granulation: the product obtained in step S3-1 is spray dried under nitrogen atmosphere protection at a drying rate of 1 kg / h at 200° C. to obtain a third precursor with a Dv50 particle size of 8 μm.
[0163] S4. Preparation of the fourth precursor:
[0164] S4-1. Hydrogen reduction: At a temperature of 550°C, with a ventilation volume of 1 L kg -1 ·min -1 Under the conditions of , the reduction was carried out by ventilation for 120 min.
[0165] S4-2, carbon deposition, in-situ growth of carbon nanotubes: the above-mentioned reduced product is subjected to carbon deposition (chemical vapor deposition) using acetylene, wherein the acetylene ventilation volume is 2 L·kg -1 ·min -1 , time is 120min, temperature is 550℃, and the fourth precursor is obtained with a specific surface area of 349m 2 / g, Dv50 particle size is 8.2μm.
[0166] S5, carbon coating:
[0167] S5-1, phenolic resin polymerization: take 1 kg of the fourth precursor, adjust the ratio of the fourth precursor to water to 1:9, add 400 g of sodium hydroxide; add 0.018 mol of phenol, add formaldehyde at a ratio of 6:7, adjust the speed to 300 r / min, the temperature to 80°C, and perform polymerization reaction for 300 min. Spray dry the particles after polymerization at 120°C, and the drying rate is 10 kg / h.
[0168] S5-2, Carbonization: Place the spray-dried powder in a rotary furnace for segmented heat treatment:
[0169] The heating curve in the first stage is 4°C / min, and the temperature is raised to 200°C and kept for 1 hour to make the phenolic resin cross-linked;
[0170] The subsequent heating curve was 4°C / min, and the temperature was raised to 600°C and kept for 12 hours for carbonization.
[0171] Among them, the nitrogen atmosphere protection gas supply rate is 1L·kg -1 ·min -1 .
[0172] S5-3, pickling: Use 1 mol / L hydrochloric acid, pickling several times with 10 times the amount of solidified material, until there is no transition metal on the surface of the material, and the magnetic foreign matter impurities are below 10 ppm.
[0173] Embodiment 2-7
[0174] The specific parameters and conditions in Examples 2-7 are the same as those in Example 1 except for the parameters in Table 1.
[0175] The schematic diagram of the structure of the silicon-carbon composite material obtained in Examples 1-7 is as follows Figure 1 As shown. The silicon-carbon composite material includes a core-shell structure, the core-shell structure includes a core and a shell covering the core, the core includes a pre-lithiated porous carbon 1 and silicon particles 2, and the silicon particles 2 are distributed in the pores of the pre-lithiated porous carbon 1; along the direction away from the core, the shell includes a passivation layer 3, a solid electrolyte layer 4 and a graphitized carbon layer 6 in sequence; wherein carbon nanotubes 5 are distributed in the passivation layer 3 and the solid electrolyte layer 4, and the carbon nanotubes 5 penetrate the solid electrolyte layer 4.
[0176] Comparative Example 1
[0177] The difference between this comparative example and Example 1 is that steps S3-1, S5-1 and S5-2 are not performed, and in step S4-2, the carbon deposition time is changed to 600 min, and the other conditions are consistent with Example 1. The obtained silicon-carbon composite material is a composite material that has been pre-lithiated but has no in-situ growth of carbon nanotubes and no graphitized carbon layer.
[0178] Comparative Example 2
[0179] The difference between this comparative example and Example 1 is that step S5 is not performed, and the other conditions are the same as those in Example 1.
[0180] The obtained silicon-carbon composite material is a composite material that has been pre-lithiated and in-situ grown carbon nanotubes but has no graphitized carbon layer.
[0181] Comparative Example 3
[0182] The difference between this comparative example and Example 1 is that steps S1-1, S3-1, S5-1 and S5-2 are not performed, and the carbon deposition time in step S4-2 is changed to 600 min. The other conditions are the same as those in Example 1.
[0183] The obtained silicon-carbon composite material is a composite material which has not been pre-lithiated, has not grown carbon nanotubes, and has no graphitized carbon layer.
[0184] Comparative Example 4
[0185] The difference between this comparative example and Example 1 is that step S3-1 is not performed, and the other conditions are the same as those in Example 1.
[0186] The obtained silicon-carbon composite material is a composite material which has been pre-lithiated, does not grow carbon nanotubes, and has a graphitized carbon layer.
[0187] Comparative Example 5
[0188] The difference between this comparative example and Example 1 is that steps S1-1 and S3-1 are not performed, and the other conditions are the same as those in Example 1.
[0189] The obtained silicon-carbon composite material is a composite material which has not been pre-lithiated, has not grown carbon nanotubes, and has a graphitized carbon layer.
[0190] Comparative Example 6
[0191] The difference between this comparative example and Example 1 is that steps S5-1 and S5-2 are replaced by acetylene coating, wherein the specific method of acetylene coating is: carbon deposition (chemical vapor deposition) is performed using acetylene, wherein the ventilation volume of acetylene is 2L·kg -1 ·min -1 , time is 120min, temperature is 550°C. Other conditions are the same as those in Example 1.
[0192] The obtained silicon-carbon composite material is a composite material that has been pre-lithiated and grown with carbon nanotubes and has no graphitized carbon layer but a conventional carbon coating layer.
[0193] Comparative Example 7
[0194] The difference between this comparative example and Example 1 is that step S1-1 is not performed, and the other conditions are the same as those in Example 1.
[0195] The obtained silicon-carbon composite material is a composite material which has not been pre-lithiated and has grown carbon nanotubes and has a graphitized carbon layer.
[0196] Comparative Example 8
[0197] The difference between this comparative example and Example 1 is that step S5-1 is not performed, and the other conditions are the same as those in Example 1.
[0198] The obtained silicon-carbon composite material is a composite material that has been pre-lithiated and has grown carbon nanotubes but has no graphitized carbon layer.
[0199] Effect Example 1
[0200] The porous carbon and silicon-carbon composite materials prepared in Examples 1-7 and Comparative Examples 1-8 were tested as follows:
[0201] (1) Element content test
[0202] Lithium content: 3 g of silicon-carbon composite material was dissolved in 20 mL of aqua regia as a test sample, and the lithium content was tested using Thermofisher ICAP 7400DUO.
[0203] Carbon content: measured using Nicolet 6700 Fourier transform infrared spectrometer (carbon and oxygen content analyzer).
[0204] Oxygen content: measured using Nicolet 6700 Fourier transform infrared spectrometer (carbon and oxygen content analyzer).
[0205] Silicon content = 1 - carbon content - oxygen content - silicon content - lithium content.
[0206] (2) Particle size Dv50 test
[0207] 0.02 g of silicon-carbon composite material was added to a 50 mL clean beaker, and 20 mL of deionized water was added. A 120 W ultrasonic cleaner was used for ultrasonic cleaning for 5 min to completely disperse the particles of the silicon-carbon composite material in the deionized water to obtain a sample dispersion.
[0208] The sample dispersion was tested using a particle size analyzer (model: MasterSizer 2000) to obtain the Dv50 particle size of the silicon-carbon composite particles.
[0209] (3) Quality of the internal carbon coating
[0210] The mass of the inner carbon coating layer = the weight after coating - the weight before coating, that is, the mass of the fourth precursor - the mass of the first precursor.
[0211] (4) Specific surface area test
[0212] Measured using Best NT-8000.
[0213] (5) Single particle strength: The test was conducted using the Yuanneng Technology single particle mechanical properties testing system SPFT2000.
[0214] (6) Powder resistivity
[0215] 5MPa powder resistivity: Use PRCD3100, place the test mold on the table of the electronic pressure tester, connect it to the resistivity tester, increase the pressure of the electronic pressure tester to 5MPa, keep the pressure constant for 60s, then release the pressure to zero, read the sample deformation height and the value of the resistivity tester (sample resistance). The conductivity is calculated according to the following formula: σ=h / (S×R), where: σ is the powder conductivity of the silicon-carbon composite material, in S / cm; h is the sample deformation height, in cm; S is the sample bottom area, which is 3.14cm 2 ; R is the sample resistance, unit is Ω. Resistivity = 1 / σ, unit is Ω·cm.
[0216] 25MPa powder resistivity: PRCD3100, place the test mold on the table of the electronic pressure tester, connect it to the resistivity tester, increase the pressure of the electronic pressure tester to 25MPa, keep the pressure constant for 60s, then release the pressure to zero, read the sample deformation height and the value of the resistivity tester (sample resistance). The conductivity is calculated according to the following formula: σ=h / (S×R), where: σ is the powder conductivity of the silicon-carbon composite material, in S / cm; h is the sample deformation height, in cm; S is the sample bottom area, which is 3.14cm 2 ; R is the sample resistance, unit is Ω. Resistivity = 1 / σ, unit is Ω·cm.
[0217] Powder resistivity retention rate = 25 MPa resistivity (Ω·cm) / 5 MPa resistivity (Ω·cm).
[0218] The above test results are shown in Table 1 and Table 2.
[0219] Effect Example 2
[0220] Preparation of pole pieces and lithium-ion batteries
[0221] This effect embodiment is to assemble the carbon-silicon composite materials provided in Examples 1-7 and Comparative Examples 1-8 into a lithium-ion battery as a negative electrode material, and the specific steps are as follows:
[0222] (1) Preparation of negative electrode slurry and electrode sheet:
[0223] The negative electrode formula is designed as CMC:PAA:SBR:SP:CNTs:silicon-carbon composite material:graphite=1:3:1:0.1:0.1:15:79.8, and the negative electrode slurry preparation process is graphite→CMC→SP→CNTs. After that, it is dispersed for 3 hours with a planetary disperser at a rotation speed of 300r / min and a revolution of 1000r / min. Then, 80% deionized water is injected, and it is dispersed for 1 hour at a rotation speed of 500r / min and a revolution speed of 600r / min. PAA is added, and it is dispersed for 1 hour at a rotation speed of 500r / min and a revolution speed of 500r / min. Then, 20% deionized water is injected, and finally SBR is added and dispersed for 1 hour at a rotation speed of 300r / min and a revolution speed of 300r / min to obtain the negative electrode slurry (solid content is 40%). The coated current collector uses 8μm thick copper foil, single-sided coating, single-sided coating active material thickness 40μm, and compaction density 1.7g / cm 3 The coating speed is 40 cm / s, followed by drying at 80° C. for 400 s. The negative electrode slurry forms a negative electrode material layer.
[0224] Among them, the test method of compaction density is: punch the pole piece into a unit circle, test the weight, subtract the weight of the copper foil, and divide it by the thickness to get the compaction density.
[0225] (2) Electrolyte
[0226] Electrolyte formula: by mass percentage, ethylene carbonate (EC) 10%, propylene carbonate (PC) 15%, diethyl carbonate (DEC) 20%, propylene propylene (PP) 30%, LiPF 6 15%, fluoroethylene carbonate (FEC) 6%, propylene sulfite (PS) 2.5%, lithium difluorooxalatoborate (LiODFB) 1.5%.
[0227] (3) Diaphragm: The diaphragm was purchased from Enjie (model: HSV7).
[0228] (4) Assembly of lithium-ion battery: With lithium metal as the counter electrode, the coated surface of the above-mentioned negative electrode sheet faces the positive electrode of the button battery, and the above-mentioned separator and electrolyte are used to assemble a CR2032 button battery.
[0229] Electrochemical performance test
[0230] The electrical performance of the button cell prepared above was tested:
[0231] (1) Expansion amount after the first lithium insertion (%): First, record the thickness of the electrode sheet without lithium insertion and the thickness of the copper foil, disassemble the first cycle battery of the 1C battery, and record the thickness of the electrode sheet after saturated lithium insertion after the first cycle. Expansion amount after the first lithium insertion (%) = [(thickness of the electrode sheet after saturated lithium insertion - thickness of the copper foil) / (thickness of the electrode sheet without lithium insertion - thickness of the copper foil) - 1] × 100.
[0232] (2) 0.8V first effect: First, assemble a CR2032 button battery. Then, discharge it to 0.000V at 0.1V / h using a constant voltage discharge method. Then, charge it to 0.8V at 0.1V / h and record the charge and discharge capacity. The first effect is calculated by dividing the discharge capacity by the charge capacity.
[0233] (3) 0.8V gram capacity: CCCV cycle charge and discharge, the voltage window is 0V-0.8V. When charging, charge at 0.2mA / h, charge to 0.8V and keep constant voltage for 5min, cut-off current is 0.01mA. When discharging, discharge at 0.2mA / h, discharge to 0V and keep constant voltage for 5min, cut-off current is 0.01mA. Gram capacity = discharge capacity / mass of active material, where the mass of active material = mass of silicon-carbon composite material + mass of graphite.
[0234] (4) Cycle number and cycle retention rate
[0235] 1C battery cycle number: At 25℃, perform CCCV cycle charge and discharge at 1000mA / h. When the battery capacity reaches 800mAh, the voltage window is 2.8V-4.2V, the cut-off current is 10mA, and the cycle number is recorded.
[0236] 3C battery cycle number: At 25°C, perform CCCV cycle charge and discharge at 3000mA / h. When the battery capacity reaches 800mAh, the voltage window is 2.8V-4.2V, and the cut-off current is 10mA. Record the cycle number.
[0237] 3C battery cycle retention rate = 3C battery cycle number / 1C battery cycle number.
[0238] (5) Number of hot box cycles and hot box cycle retention rate
[0239] 1C battery hot box cycle number: At 45℃, perform CCCV cycle charge and discharge at 1000mA / h. When the battery capacity reaches 800mAh, the voltage window is 2.8V-4.2V, the cut-off current is 10mA, and the cycle number is recorded.
[0240] 3C battery hot box cycle number: At 45°C, perform CCCV cycle charge and discharge at 3000mA / h. When the battery capacity reaches 800mAh, the voltage window is 2.8V-4.2V, the cut-off current is 10mA, and the cycle number is recorded.
[0241] 1C battery hot box cycle retention rate = 1C battery hot box cycle number / 1C battery cycle number.
[0242] 3C battery hot box cycle retention rate = 3C battery hot box cycle number / 1C battery cycle number.
[0243] (6) Number of bubbles
[0244] Number of bubbles per square meter: After the stirring of the negative electrode slurry is completed and stagnant for 20 minutes, open the stirring tank, calculate the cross-sectional area of the stirring tube and the number of bubbles on the surface, and calculate the number of bubbles on the surface per square meter, that is, the number of bubbles per square meter = number of bubbles on the surface / cross-sectional area of the stirring tube.
[0245] The above test results are shown in Table 2 and Table 3.
[0246] Table 1
[0247]
[0248]
[0249] Table 2
[0250]
[0251] Table 3
[0252]
[0253]
[0254] Note: “ / ” in Table 1 and Table 2 means that the condition parameter is not involved in the specific experiment.
[0255] In Examples 1-7 of the present invention, the obtained silicon-carbon composite material has good conductivity, high mechanical strength, and excellent expansion inhibition performance. Specifically, the single particle strength can reach more than 10MPa, the 5MPa powder resistivity can reach less than 6.2Ω·cm, the 25MPa powder resistivity can reach less than 5.1Ω·cm, and the powder resistivity retention rate can reach more than 0.46; when the composite silicon-carbon material is used as the negative electrode material, the number of bubbles per unit square meter of the negative electrode slurry can be less than 121, the expansion inhibition performance of the pole piece is excellent (the first cycle lithium insertion expansion amount can be less than 17%), and the prepared lithium ion battery can take into account excellent first efficiency, gram capacity and cycle performance. Specifically, the number of 1C battery cycles can be higher than 1000 cycles. On this basis, the 0.8V first efficiency can reach more than 93%, the 0.8V gram capacity can reach more than 1430mAh / g, the 3C battery cycle retention rate can reach more than 0.6, the 1C battery hot box cycle retention rate can reach more than 0.85, and the 3C battery hot box cycle retention rate can reach more than 0.6.
[0256] Based on Example 1, the silicon-carbon composite material obtained in Comparative Example 1 has no carbon nanotubes and no graphitized carbon layer, and the first-cycle lithium insertion expansion of the pole piece is relatively high. Although the 0.8V first efficiency of the prepared lithium-ion battery is equivalent and the 0.8V gram capacity is relatively high, the 1C battery cycle number, 3C battery cycle retention rate, 1C battery hot box cycle retention rate and 3C battery hot box cycle retention rate are all significantly deteriorated.
[0257] Based on Example 1, the composite silicon-carbon materials obtained in Comparative Examples 2 and 8 have no graphitized carbon layer, and the first-cycle lithium insertion expansion of the pole piece is poor. Although the 0.8V gram capacity of the prepared lithium-ion battery is high, the 0.8V first efficiency of the prepared lithium-ion battery is poor, and the 1C battery cycle number, 3C battery cycle retention rate, 1C battery hot box cycle retention rate and 3C battery hot box cycle retention rate are all significantly deteriorated.
[0258] On the basis of Example 1, the silicon-carbon composite material obtained in Comparative Example 3 has no pre-lithium, no carbon nanotubes and no graphitized carbon layer, the first-cycle lithium insertion expansion of the pole piece is poor, the 0.8V first efficiency of the prepared lithium-ion battery is significantly deteriorated, the 0.8V gram capacity is low, and the 1C battery cycle number, 3C battery cycle retention rate, 1C battery hot box cycle retention rate and 3C battery hot box cycle retention rate are all significantly deteriorated.
[0259] On the basis of Example 1, the silicon-carbon composite material obtained in Comparative Example 4 does not have carbon nanotubes, and the first-cycle lithium insertion expansion of the pole piece is improved. Although the 0.8V first efficiency and 0.8V gram capacity of the prepared lithium-ion battery are relatively high, the 1C battery cycle number, 3C battery cycle retention rate, 1C battery hot box cycle retention rate and 3C battery hot box cycle retention rate of the prepared lithium-ion battery are all greatly reduced.
[0260] On the basis of Example 1, the silicon-carbon composite material obtained in Comparative Example 5 has no pre-lithium and no carbon nanotubes, the first-cycle lithium insertion expansion of the pole piece is increased, the 0.8V first efficiency of the prepared lithium-ion battery is significantly deteriorated, the 0.8V gram capacity is low, and the 1C battery cycle number, 3C battery cycle retention rate, 1C battery hot box cycle retention rate and 3C battery hot box cycle retention rate are all significantly reduced.
[0261] On the basis of Example 1, the silicon-carbon composite material obtained in Comparative Example 6 uses a conventional carbon layer instead of a graphitized carbon layer, and the first-cycle lithium insertion expansion of the pole piece is relatively high. Although the 0.8V first efficiency and 0.8V gram capacity of the prepared lithium-ion battery are relatively high, the 1C battery cycle number, 3C battery cycle retention rate, 1C battery hot box cycle retention rate and 3C battery hot box cycle retention rate are all significantly deteriorated.
[0262] Based on Example 1, the silicon-carbon composite material obtained in Comparative Example 7 has no pre-lithium, the first-cycle lithium insertion expansion of the pole piece is high, the 0.8V first efficiency of the prepared lithium-ion battery is significantly deteriorated, the 0.8V gram capacity is low, and the 1C battery cycle number, 3C battery cycle retention rate, 1C battery hot box cycle retention rate and 3C battery hot box cycle retention rate are all significantly deteriorated.
[0263] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing a silicon-carbon composite material, characterized in that: It includes the following steps: S1, using chemical vapor deposition to deposit silicon on the pre-lithiated porous carbon to obtain a first precursor; S2, coating the surface of the first precursor with a passivation layer to obtain a second precursor; S3, adding an alkaline reagent to a mixed solution containing the second precursor, a transition metal salt and a solvent, and drying to obtain a third precursor; S4, performing carbon deposition on the third precursor by chemical vapor deposition to in-situ grow carbon nanotubes to obtain a fourth precursor; S5, subjecting the slurry containing the fourth precursor, the phenolic compound and the aldehyde compound to a polymerization reaction, and then subjecting the slurry to a carbonization treatment after drying, to obtain the silicon-carbon composite material.
2. The silicon-carbon composite material according to claim 1, characterized in that: In step S1, the pre-lithiation method comprises mixing the porous carbon and a lithium source and heating them; wherein, Preferably, the lithium source includes one or more of phenyllithium, lithium chloride, lithium sulfate, lithium carbonate, lithium acetate, lithium bromide, lithium iodide, lithium nitrate, lithium phosphate, lithium sulfate, lithium bisulfite, lithium citrate and lithium hydride, for example, phenyllithium; Preferably, the heating temperature is between the melting point of the lithium source and the decomposition temperature of the lithium source; Preferably, the mass ratio of the porous carbon to the lithium source is 1:(0.1-0.6), for example, 1:0.42; Preferably, the pre-lithiation process is carried out under the protection of an inert gas; the inert gas is, for example, argon.
3. The silicon-carbon composite material according to claim 1, characterized in that: Step S5 satisfies one or more of the following conditions ag: a. The molar ratio of the phenolic compound to the aldehyde compound is 1:(1-2), for example, 6:7; b. The mass ratio of the fourth precursor to the phenolic compound is (0.1-120), preferably 100:(15-120), for example, 100:17, 100:34, 100:68, 100:85, 100:102 or 100:119; c. The polymerization reaction temperature is 40-100° C., for example, 80° C.; d. The polymerization reaction time is 6-600 min, for example, 300 min; e. The phenolic compound is phenol, and the aldehyde compound is formaldehyde; f. The pH of the slurry is 1-3, or the pH of the slurry is 12-14; g. The slurry also includes alkali or acid.
4. The silicon-carbon composite material according to claim 1, characterized in that: Step S1 and step S2 satisfy one or more of the following conditions af: a. In step S1, the temperature of silicon deposition is 400-800° C., for example, 500° C.; b. In step S1, the silicon deposition time is 4-20 hours, for example, 10 hours; c. In step S1, the silicon source for the silicon deposition includes silane, and the silane preferably includes one or more of monosilane, disilane, trisilane and tetrasilane; d. In step S1, during the silicon deposition process, the ventilation volume of the silicon source is 0.04-0.4 L·kg -1 min -1 ; e. In step S1, the gas source for silicon deposition includes a silicon source and a carrier gas; wherein the volume ratio of the silicon source to the carrier gas is 1:(2-6), for example, 1:4; f. In step S2, the passivation layer includes a carbon layer and / or an oxide layer; preferably, the carbon layer is obtained by carbon deposition using a chemical vapor deposition method.
5. The silicon-carbon composite material according to claim 1, characterized in that: Step S3 and step S4 satisfy one or more of the following conditions: a. In step S3, the transition metal salt comprises a divalent salt and / or a trivalent salt of a transition metal; preferably, the transition metal salt comprises a divalent salt and a trivalent salt of iron, such as ferrous sulfate and ferric chloride; the molar ratio of the divalent salt and the trivalent salt of iron is preferably (2-4):1; b. In step S3, the content of the transition metal salt is 0.01-0.3 mol / kg, for example, 0.06 mol / kg; c. In step S3, the alkaline reagent includes a weak base reagent and / or a strong base reagent, preferably ammonia water; d. In step S3, the mass ratio of the alkaline reagent to the solvent is (1-1000):100, for example, 1:1; e. In step S3, the mixed solution further comprises a complexing agent; wherein the complexing agent comprises an organic acid and / or an organic acid salt, preferably comprises one or more of acetic acid, citric acid, EDTA and salts thereof, for example, comprises one or more of ferric acetate, sodium acetate, ferric citrate, sodium citrate and EDTA; the mass ratio of the complexing agent to the second precursor is preferably 1:(5-1000), for example, 1:10; f. In step S3, the alkaline reagent is added dropwise, and the dropping speed of the alkaline reagent is 1-1000 mL / min, for example, 10 mL / min; g. In step S3, the operation of adding the alkaline reagent is performed under a protective atmosphere; h. In step S3, after adding the alkaline reagent and before drying, an alcoholization step is further included; wherein the alcoholization temperature is preferably 50-100° C., such as 90° C.; and the alcoholization time is preferably 0.5-25 h, such as 5 h; i. In step S3, the Dv50 particle size of the third precursor is 4-20 μm, for example, 8 μm; j. In step S4, before the carbon deposition, the step of reducing the third precursor is also included; Wherein, the reduction temperature is preferably 400-800°C, for example 550°C; The reduction is preferably carried out in a reducing atmosphere; the reducing atmosphere is preferably hydrogen; the ventilation volume of the reducing atmosphere is preferably 0.1-10 L·kg -1 ·min -1 , for example 1L kg -1 ·min -1 ; Wherein, the reduction time is preferably 60-300 min, for example 120 min; k. In step S4, the carbon source of the carbon deposition includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates, such as acetylene; 1. In step S4, during the carbon deposition process, the ventilation volume of the carbon source is 0.2-20 L·kg -1 ·min -1 , for example 2L·kg -1 ·min -1 ; m. In step S4, the carbon deposition time is 60-300 min, for example, 120 min; n. In step S4, the temperature of the carbon deposition is 400-800°C, for example, 550°C.
6. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared by the preparation method of any one of claims 1 to 5.
7. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material includes a core-shell structure, which includes an inner core and an outer shell covering the inner core, wherein the inner core includes pre-lithiated porous carbon and silicon particles, and the silicon particles are distributed in the pores of the pre-lithiated porous carbon; along the direction away from the inner core, the outer shell includes a passivation layer, a solid electrolyte layer and a graphitized carbon layer in sequence; wherein carbon nanotubes are distributed in the passivation layer and the solid electrolyte layer and the carbon nanotubes penetrate the solid electrolyte layer.
8. The silicon-carbon composite material according to claim 7, characterized in that: It meets one or more of the following conditions: a. The Dv50 particle size of the silicon-carbon composite material is 8-10 μm, preferably 8-9 μm, for example, 8.3 μm, 8.4 μm, 8.5 μm, 8.7 μm or 8.9 μm; b. The specific surface area of the silicon-carbon composite material is 1-2m 2 / g, for example, 1.1m 2 / g, 1.2m 2 / g, 1.5m 2 / g or 1.6m 2 / g; c. The carbon content of the silicon-carbon composite material is 50%-60%, for example, 51.8%, 53.1%, 53.8%, 53.9%, 55.3%, 58.1% or 58.7%; d. The oxygen content of the silicon-carbon composite material is 0.2%-1.6%, for example, 0.3%, 0.5%, 0.7%, 0.8%, 1.1% or 1.4%; e. The silicon content of the silicon-carbon composite material is 30%-50%, preferably 35%-45%, for example, 35.4%, 36.1%, 39.1%, 40.7%, 40.5%, 41.6%, 43.5%; f. The lithium content of the silicon-carbon composite material is 4%-5%, for example, 4.3%, 4.4%, 4.5%, 4.6% or 4.8%; g. The single particle strength of the silicon-carbon composite material is 5-25 MPa, preferably 10-20 MPa, for example, 10.4 MPa, 14.3 MPa, 16.6 MPa, 16.9 MPa, 17.2 MPa, 17.5 MPa or 18.2 MPa.
9. Use of the silicon-carbon composite material as claimed in any one of claims 6 to 8 as a negative electrode material in a lithium-ion battery.
10. A lithium ion battery, characterized in that: It comprises the silicon-carbon composite material as described in any one of claims 6 to 8.
Citation Information
Patent Citations
Silicon-carbon composite material, preparation method thereof, negative plate and lithium secondary battery
CN115513432A
Silicon-carbon composite material with silicon-carbon alternate multi-level structure and preparation method and application thereof
CN118929633A
Pre-lithiated silicon-carbon composite material and preparation method thereof
CN118983426A
Nano-silicon-carbon composite material, and preparation method therefor and use thereof
WO2024120302A1
Cited By
Lithium ion battery electrode material and preparation method thereof
CN121260767A
Silicon negative electrode material, preparation method and lithium ion battery
CN121260768A